Do firm characteristics affect price discovery? Evidence from Chinese cross-listed stocks - Yen-Sheng Lee; Yi-Heng Tseng (Economic Review: Journal of Economics and Business, 2021)
This study examines the price movement relationship for Chinese firms that cross-list their shares on the Hong Kong Stock Exchange and the Shanghai Stock Exchange or Shenzhen Stock Exchange in mainland China. We estimate the coefficients of adjustment speed between the two markets by conducting a unit root test and apply a vector error correction model for the price series of our 55 sample firms. The majority of the adjustment speeds of the sample firms are statistically significant, implying that the stock prices of companies cross-listed in both markets respond to each other. Our results are in line with the literature on price discovery that the Hong Kong and mainland China financial markets are informationally linked. We regress the coefficients of adjustment speed on a spectrum of firm-specific variables. The cross- sectional regression results indicate that the effective spread that proxies for the liquidity factor partially accounts for the speed of price adjustment. Our study adds to the existing literature on the price discovery process within Chinese stock markets.
Keywords: G12; G15; 330; cross-listed stocks; price discovery; vector error correction model